2000
DOI: 10.1034/j.1600-0706.2000.900217.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the reduction of plant diversity for litter decomposition: effects through litter quality and microenvironment

Abstract: Consequences of the reduction of plant diversity for litter decomposition: effects through litter quality and microenvironment. -Oikos 90: 357 -371.Decomposition of plant litter is a key process for the flow of energy and nutrients in ecosystems that may be sensitive to the loss of biodiversity. Two hypothetical mechanisms by which changes in plant diversity could affect litter decomposition are (1) through changes in litter species composition, and (2) by altering the decomposition microenvironment. We tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
241
5
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(278 citation statements)
references
References 61 publications
24
241
5
8
Order By: Relevance
“…Species differ in aboveground litter quality, but the pattern of soil mineral nitrate availability along the species richness gradient is only weakly reflected in the aboveground litter quality gradient. Thus, higher species richness results in an averaging of the species differences in aboveground litter quality without significant interactions along a species richness gradient, as reported by Wardle et al (1997) and Hector et al (2000). This supports the hypothesis that litter production increases with higher plant species richness because of increased productivity.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Species differ in aboveground litter quality, but the pattern of soil mineral nitrate availability along the species richness gradient is only weakly reflected in the aboveground litter quality gradient. Thus, higher species richness results in an averaging of the species differences in aboveground litter quality without significant interactions along a species richness gradient, as reported by Wardle et al (1997) and Hector et al (2000). This supports the hypothesis that litter production increases with higher plant species richness because of increased productivity.…”
Section: Resultssupporting
confidence: 77%
“…However, litter decomposition studies have not shown consistent effects of plant species diversity on decomposition rates (Blair et al 1990;Elliott et al 1993;Fyles and Fyles 1993;Hart et al 1993;Klemmedson 1991;Knops et al 1996;Kochy and Wilson 1997;Taylor et al 1989;Williams and Alexander 1991). Four recent studies have specifically examined the effect of litter diversity on decomposition (Bardgett and Shine 1999;Finzi and Canham 1998;Hector et al 2000;Wardle et al 1997). Finzi and Canham (1998) and Hector et al (2000) found significant, but non-additive effects and Wardle et al (1997) found that biodiversity itself was not a significant determinant of decomposition rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3b), short-term laboratory studies indicated a positive e ect of earthworms on nitri cation in soils containing beech litter (Scheu 1997). While the e ect diminished in mixed litter treatments (beech, nettle) because of N transfer among litter species, other studies reported increased mineralization and leaching due to mixing of soil organic matter and mineral soil (Hector et al 2000;Xiong et al 2014). …”
Section: E Ects Of Soil Fauna On N Uxesmentioning
confidence: 98%
“…Measures of community functioning (e.g., productivity and nutrient cycling) have typically been found to be more consistently associated with functional diversity than with species richness Influence of fire history and soil properties on plant species richness and functional diversity in a neotropical savanna Hector et al 2000). There is growing evidence that functional diversity strongly determines ecosystem-level processes, such as resource acquisition, nutrient cycling, and productivity (e.g., Hooper & Vitousek 1997;Díaz & Cabido 2001;Hooper et al 2005).…”
Section: Introductionmentioning
confidence: 99%